Black or red phosphorus yields the same blue phosphorus film. Issue 43 (26th October 2022) - Sala, Alessandro; Caporali, Maria; Serrano-Ruiz, Manuel; Armillotta, Francesco; Vesselli, Erik; Genuzio, Francesca; Menteş, Tevfik Onur; Locatelli, Andrea; Comelli, Giovanni; Africh, Cristina; Verdini, Alberto
Abstract : After the discovery of graphene, many other 2D materials have been predicted theoretically and successfully prepared. In this context, phosphorene is emerging as a viable contender in the field of (2D) semiconductors. Abstract : After the discovery of graphene, many other 2D materials have been predicted theoretically and successfully prepared. In this context, single-sheet black phosphorus – phosphorene – is emerging as a viable contender in the field of (2D) semiconductors. Phosphorene offers high carrier mobility and an anisotropic structure that gives rise to a modulation of physical and chemical properties. This opens the way to many novel and fascinating applications related to field-effect transistors and optoelectronic devices. In previous studies, a single layer of blue phosphorene intermixed with Au atoms was grown using purified black phosphorus as a precursor. Starting from the observation that phosphorus vapor mainly consists of P clusters, in this work we aimed at obtaining blue phosphorus using much less expensive purified red phosphorus as an evaporant. By means of microscopy, spectroscopy and diffraction experiments, we show that black or red phosphorus deposition on Au(111) substrates yields the same blue phosphorus film.